Diffusion tensor imaging in neonatal encephalopathy: a systematic review. Issue 5 (10th December 2019) - Dibble, Megan; O'Dea, Mary Isabel; Hurley, Tim; Byrne, Angela; Colleran, Gabrielle; Molloy, Eleanor J; Bokde, Arun Lawrence Warren
Abstract : Background and objective: Diffusion tensor imaging (DTI) during the first few days of life can be used to assess brain injury in neonates with neonatal encephalopathy (NE) for outcome prediction. The goal of this review was to identify specific white matter tracts of interest that can be quantified by DTI as being altered in neonates with this condition, and to investigate its potential prognostic ability. Methods: Searches of Medline and the Cochrane Database of Systematic Reviews were conducted to identify studies with diffusion data collected in term-born neonates with NE. Results: 19 studies were included which described restricted diffusion in encephalopathic neonates as compared with healthy controls, with the posterior limb of the internal capsule and the genu and splenium of the corpus callosum identified as particular regions of interest. Restricted diffusion was related to adverse outcomes in the studies that conducted a follow-up of these infants. Conclusions: Obtaining diffusion measures in these key white matter tracts early in life before pseudonormalisation can occur can not only identify the extent of the damage but also can be used to examine the effectiveness of treatment and to predict neurodevelopmental outcome.